Does the use of antioxidant agents after dental bleaching compromise the aesthetic results of ceramic laminate veneers? - Strazzi-Sahyon, Henrico Badaoui [UNESP]; Briso, André Luiz Fraga [UNESP]; Santos, Paulo Henrique dos [UNESP] (Elsevier, 2023)
PURPOSE: This in vitro study aimed to evaluate the aesthetic compromise generated in adhesive interface of ceramic laminate veneer luted after tooth bleaching and the use of antioxidant agents. Thus, the chromatic coordinates and whitening index (WID) were evaluated, comparing whiteness changes (ΔWID) results to perceptibility and acceptability thresholds. MATERIAL AND METHODS: In total, 88 bovine enamel samples (7 × 8 × 4 mm; n = 8) were submitted to the ceramic laminate veneer luting protocol according to surface treatment (unbleached and bleached enamel), antioxidant agents (control; 10% ascorbic acid and 10% α-tocopherol), and luting periods (after 24 h and after 14 days). To lute IPS e.max ceramic restorations (7 × 8 × 0.6 mm), Tetric N-Bond Universal adhesive system and Variolink Aesthetic LC resin cement were used. An ultraviolet-visible spectrophotometer (UV-VIS) was utilized to measure CIE L*a*b* coordinates prior to and after UV-B artificial accelerated aging for 252, 504, and 756 h. L*, a*, and b* axes were evaluated separately, and the whitening stability (ΔWID) effect was assessed by varying the whiteness index for dentistry (WID). The 50:50% visual threshold was used to evaluate ΔWID values (whiteness perceptibility [WPT] and whiteness acceptability [WAT]). Color parameters changes (ΔL*Δa*Δb*), WID, and ΔWID data were subjected to 2-way repeated measures ANOVA followed by Tukey's test (α = 0.05). RESULTS: Different UV-aging periods influenced the chromatic coordinates, WID, and ΔWID of the ceramic restorations regardless of the bleaching treatment, antioxidant solutions and luting periods (P < .05). In general, ΔWID values after UV-aging periods were above perceptibility and acceptability thresholds (WPT = 0.72 and WAT = 2.62, respectively) for all experimental groups (P < .05). Unbleached and 10% ascorbic acid-treated enamels luted after 14 days of the antioxidant action exhibited lower ΔL* and Δb* values, while control group showed lower Δa* values. All experimental groups showed similar performance on ΔWID compared to the control group, regardless of the UV-aging period analyzed (P > .05). CONCLUSION: α-tocopherol is a suitable antioxidant solution to be used 24 h post enamel bleaching not compromising clinical acceptability of ceramic laminate veneers. CLINICAL RELEVANCE: The adhesive interface of ceramic laminate veneers may appear darker after the use of antioxidant agents affecting the clinical acceptability of the restorations.